Study on Knowledge of Infection Control Practice of Healthcare Workers - Gazi Reaz Rahman; Amiya Bhaumik (Wolters Kluwer Medknow Publications, 2024)
Background: Healthcare-associated infections (HAIs), also known as nosocomial infections, are a significant risk in hospitals, leading to increased morbidity and mortality among patients due to poor hygiene practices. Materials and Methods: This descriptive study involved 350 participants from Wuhan's private hospitals. Respondents answered a questionnaire distributed in person or via email, and data were analyzed using SPSS version 25.0. Results: Analysis revealed a knowledge gap among healthcare workers in infection control, affecting their ability to maintain hospital cleanliness. Education levels were assessed, showing that 60% of participants held diplomas or higher qualifications. Conclusion: The study highlights the urgent need for enhanced training and information dissemination on infection control practices among healthcare staff. Identifying this knowledge and practice gap is crucial for improving hospital hygiene and reducing HAI incidence.